High Blood Pressure, an Epidemic Inadequately Diagnosed and Poorly Controlled: A Community-Based Survey in Kinondoni District, Dar Es Salaam Tanzania (Global Journal of Medical Research, 2016)
Background: Population ageing, rapid urbanization and unhealthy lifestyles continue to transform global health. The prevalence of hypertension which currently affects over a billion people globally is rapidly increasing while the rates of its awareness, treatment and control remain low especially in developing nations. We aimed to determine the prevalence, awareness, control and associated factors for hypertension among residents of the largest district in Dar es Salaam. Methods: We conducted a cross-sectional, community-based survey in January 2016, 1831 persons were recruited. Physical activity was assessed using the physical activity vital sign scale (PAVS) and alcohol dependence was assessed by the CAGE questionnaire. Trained personnel measured and recorded blood pressure and anthropometric measures. Hypertension was defined according to the 7th Report of the Joint National Committee (JNC 7) or use of blood pressure lowering medications. Multivariate logistic regression analyses were performed to assess for factors associated with high blood pressure. Results: The mean age of participants was 43.6 years and 63.5% were women. 1.1% were current smokers, 5.3% were alcohol dependent, 64.3% had excess body weight, and 67% were physically inactive. 63.3% of individuals had hypertension, and 51% of these were unaware of their hypertensive status. Among those with hypertension awareness, 17.5% had their hypertension controlled. Age #x2265;40, male sex and BMI #x2265;25 were strongly associated with a newly diagnosed hypertension status, (OR 5.7, 95% CI 4.2-7.8, plt;0.001; OR 1.6, 95% CI 1.1-2.2, plt;0.01; and OR 2.9, 95% CI 2.1-4.1, plt;0.001 respectively). Conclusions: Our findings suggest that excess body weight is a single modifiable risk factor strongly associated with high blood pressure. Majority of persons with high blood pressure are undetected and thus unaware of their hypertensive status. Furthermore, hypertension control rates are very low.
Keywords: high blood pressure; hypertension; excess body weight; physical inactivity; hypertension control; hypertension awareness; obesity